Impact of population ageing on education level and average monthly salary - Čepar, Žiga (Managing global transitions, 2015)
Population ageing is a contemporary problem, which does not only mean changing demographic structures, but also affects economy. Based on our research we cannot reject our main research thesis that population ageing has a significant impact on human capital in Slovenia. Using multiple regression analysis, on cross-section data of Slovenian municipalities, we cannot reject our first hypothesis that population ageing in Slovenia leads to lower education level and our second hypothesis that population ageing leads to lower average net monthly salary. Main contribution of this research therefore is the finding and empirical confirmation of the specific impact that population ageing has on human capital based on specific case of Slovenian cross section data. Results of the research imply that some measures have to take place in order to mitigate the unfavourable effects of population ageing on human capital.
Keywords: education level; izobrazbena stopnja; average salary; staranje prebivalstva; človeški kapital; population ageing; human capital; Slovenija; občine; Slovenia; municipalities